Sistem Aerasi dengan Pengendalian PID untuk Optimasi Kadar Oksigen Terlarut pada Kolam Ikan - Nur Kamilah, Rima; Hiron, Nurul; Maulana, Firmansyah (Fuse-teknik Elektro, 2025)
Dissolved oxygen (DO) levels are an important parameter in fish farming because they directly affect fish metabolism, growth, and survival. This study designed an automatic aeration system based on Proportional–Integral–Derivative (PID) control using a LilyGO T-Relay microcontroller and an AC Dimmer module. The system is equipped with DO, pH, and temperature sensors that monitor water quality in real-time and send data to Google Sheets via a Wi-Fi connection. Tests were conducted at four DO setpoints: 4 mg/L, 5.3 mg/L, 6 mg/L, and 7 mg/L. The results showed that the system was able to maintain DO with an average error of 2.02% and energy savings of up to 99.5%, with the lowest power consumption of 0.45 Wh at the 4 mg/L setpoint. This system is considered effective in maintaining water quality while increasing energy efficiency in fish farming.